Health, wellness and medical tourism: A conceptual approach - Quintela, Joana (2019)
Nowadays, health, wellness and medical tourism are recognized as one of the most developed and growing sector of today’s thriving tourism industry that has increased its activity worldwide, due to a lot of social and economic circumstances that leads people to achieve and pursue a better quality of life. However, these kind of tourism face a multitude of challenges and one of that challenges is the discrepance on its different conceptual approaches and definitions. A literature review on this topic with a descriptive, comparative and exploratory nature was conducted, building a theoretical framework on this field of study. Units of meaning for the definition of the concept categories were elected, which allowed to reflect and sintetize the different approaches to the topic. This analysis brought other perspectives of identification and description of distinct themes, including a few issues about health, wellness, medical tourism, wellbeing and quality of life. Therefore, the main goal of this paper is to summarize and clarify this complex and sweeping concept that assumes in a prominent role in the global context of tourism and results in a concise overview of the literature produced on the subject towards a small contribution to a better understanding of the concept.